Prevalence of homosexual and bisexual orientation in patients with borderline personality disorder and associated factors – a systematic review and meta-analysis - Shu, Ying Chi Camille; Lau, Ka To; Ho, Cyrus Su Hui (Frontiers in Psychiatry, 2024)
IntroductionThis meta-analysis aimed to quantitatively evaluate the association between homosexual and bisexual orientation and borderline personality disorder (BPD), including factors contributing to the association and clinical outcomes of homosexual and bisexual patients with BPD. MethodsWe systematically searched PUBMED, PsycINFO, Cochrane Library, MEDLINE, EMBASE and Web of Science for cross-sectional or cohort studies comparing the prevalence of homosexual and bisexual orientation amongst patients with BPD and controls. ResultsOur search identified 7 eligible studies, with a total sample case of 636 subjects with BPD and 535 subjects without BPD. Patients with BPD had a significantly higher likelihood of homosexual and bisexual orientation (Risk ratio [RR] 3.39, 95%CI 1.88-6.12) with a pooled prevalence of 28% (95% CI 0.24-0.31; I2 73%; 7 studies, 1171 participants). Subgroup analyses validated that BPD was independently associated with higher prevalence of both homosexual (RR 8.51, 95% CI 3.36-21.54) and bisexual orientation (RR 3.82, 95% CI 1.81-8.04), but no gender difference was yielded. Childhood sexual abuse (CSA) was associated with the development of homosexual and bisexual orientation in patients with BPD. DiscussionPoorer clinical outcomes, including physical and mental health, were associated with BPD status. Further studies are necessary to evaluate the feasibility and efficacy of sexual minority-specific treatment for these patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=538356, identifier CRD42024538356.